Adipose-derived mesenchymal stromal/stem cells in type 1 diabetes treatment - Vanshika Sood; Hannah Ricioli; George Chigozie Njoku; Rosita Primavera; Susana Dietrich; Avnesh S. Thakor; Flemming Pociot; Reza Yarani (Communications Biology)
Abstract Adipose tissue-derived mesenchymal stromal/stem cells (ADMSCs) represent a novel therapeutic intervention for Type 1 Diabetes (T1D). The attractiveness of ADMSCs is characterized by their immunomodulatory activities, regenerative properties, and relative ease of access. ADMSC therapies in animal models and clinical trials have revealed decreased insulin dependence, increased β cell mass, and improved islet graft acceptance. Despite their potential, challenges in quality control, small-scale investigations, functional heterogeneity, and standardization limit the application of these therapies. This review synthesizes the current knowledge and recent outcomes of ADMSC therapies in treating T1D and highlights areas that need further investigation.